The Effect of Business Capital, Length of Business, Working Hours and Business Location on Micro-scale Business Income in Udayana Park, Mataram City - Yuliano Adrimarsith Dwian Balo; M. Irwan; Emi Salmah (Tinta Emas Institute, 2024)
This research was conducted at Udayana Park, Mataram City and aims to analyse the effect of business capital, length of business, working hours, and business location on micro-scale business income in Udayana Park, the data used in this study are primary data, obtained through observation, questionnaires, and documentation on objects that are relevant to this research. The results showed that the test results, business capital partially had a significant effect on business income (0.0011 <0.05). Duration of business has a significant effect on business income (0.0445 <0.05), then the variable working hours has a significant effect on income (0.0031 <0.05). While the business location has no significant effect on business income (0.9162> 0.05), then the results of the f test simultaneously show that the variables of business capital, length of business, working hours, and business location have a significant effect on micro-scale business income in Udayana Park, Mataram City. The results of the Adjusted R-squared calculation obtained a value of 0.352577 or 35.2%. This means that the contribution of business capital variables, length of business, working hours, and business location to micro-scale business income in Udayana Park, Mataram City is 35.2%, the remaining 64.8% is determined by other variables outside this study.